(untitled) (International Journal on Stereo & Immersive Media, 2019)
Produced by different techniques and processes, photographs have become means of visual knowledge, historic sources for the study and transdisciplinary research of multiple aspects of the history, culture, memory and identity of societies. The cultural heritage of a people finds, in the photographic image and in its artefacts, visual memory preserved. My topic addresses precisely the moment prior to the dissemination of photography throughout the world. A moment when photography, or the idea of it, was still something that some researchers, very few, some distant from others, thought about and experimented with a similar aim: that of making permanent the images of the camera obscura. I am referring to the first decades of the 19th century and, more specifically, to the 1830s. Historic approaches, when they seek to analyse the possible causes that determine discoveries, usually repeat “that the idea was in the air”. Actually, this statement explains very little of the phenomenon, at least in the instance we will address here. Resumo: Produzidas por diferentes técnicas e processos, as fotografias se prestam como meios de conhecimento visual, fontes históricas para o estudo e a pesquisa transdisciplinar de múltiplos aspectos da história, cultura, memória e identidade das sociedades. O patrimônio cultural de um povo tem na imagem fotográfica e nos seus artefatos, a memória visual preservada. Meu tema se refere justamente ao momento anterior à expansão da fotografia pelo mundo. A um momento em que a fotografia, ou a ideia dela, era ainda algo que alguns pesquisadores, muito poucos, uns afastados dos outros, pensavam e experimentavam com um propósito semelhante: o de tornar permanentes as imagens da camera obscura. Me refiro às primeiras décadas do século XIX e, mais precisamente, à década de 1830. As abordagens históricas quando buscam analisar as possíveis causas determinantes das descobertas costumam repetir “que a ideia estava no ar”. Na realidade essa frase explica muito pouco sobre o fenômeno, pelo menos no caso que abordaremos aqui.